2022
DOI: 10.1093/neuonc/noac043
|View full text |Cite
|
Sign up to set email alerts
|

Prospective validation of a new imaging scorecard to assess leptomeningeal metastasis: A joint EORTC BTG and RANO effort

Abstract: Background Validation of the 2016 RANO MRI scorecard for leptomeningeal metastasis failed for multiple reasons. Accordingly, this joint EORTC Brain Tumor Group and RANO effort sought to prospectively validate a revised MRI scorecard for response assessment in leptomeningeal metastasis. Methods Coded paired cerebrospinal MRI of 20 patients with leptomeningeal metastases from solid cancers at baseline and follow-up after treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…Radiological assessment was based on the EORTC/RANO revised LM scorecard 3 and performed by a dedicated neuroradiologist at DFCI (HL) and Duke (CL). The scorecards were completed for each patient at each MRI re-evaluation; BrMs response was also reported (Supplementary Table 1).…”
Section: Data Collection and Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…Radiological assessment was based on the EORTC/RANO revised LM scorecard 3 and performed by a dedicated neuroradiologist at DFCI (HL) and Duke (CL). The scorecards were completed for each patient at each MRI re-evaluation; BrMs response was also reported (Supplementary Table 1).…”
Section: Data Collection and Evaluationmentioning
confidence: 99%
“…Between 5-15% of patients with metastatic breast cancer (MBC) develop leptomeningeal metastases (LM) 1,2 with approximately 60% having no parenchymal brain metastases (BrMs) 3 . The presence of LM has a drastic impact on patients' function and quality of life, leading to poor survival outcomes, with a median survival of only 4.4 months in human epidermal growth factor receptor 2-positive (HER2+) MBC 4 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…MRI is a qualitative diagnostic tool and may have limitations of inter-reader variability and nonspecific findings 6 ; however, a recent report from EORTC BTG and RANO effort showed the usefulness of a new imaging scorecard. 9 , 10 Advances in technology, including the clinical usage of high-magnetic-field machines and pre- and post-contrast T2 fluid-attenuated inversion recovery (FLAIR) MRI, may refine and improve the imaging assessment of LM in the future. 32 We should be careful when using MRI to assess various primary malignancies, as Prommel et al 33 showed that the sensitivities of cytology and MRI were significantly influenced by the primary tumor type as solid or hematological malignancies.…”
Section: Discussionmentioning
confidence: 99%
“… 8 The diagnosis of LM is currently based on the three examination modalities: neurological evaluations, neuroimaging and cerebrospinal fluid (CSF) cytology. 9 , 10 However, the performance of these modalities is reportedly suboptimal. 5 CSF cytology remains the gold standard for the diagnosis of LM, but has been of low sensitivity.…”
mentioning
confidence: 99%